(untitled) (Al-Ilmu, 2025)
Islamic Religious Education (IRE) plays a strategic role in building religious moderation amid Indonesia’s diverse society. This study examines the role of IRE in strengthening religious moderation through a systematic literature review of 20 scientific articles published between 2020 and 2025. The results show that PAI contributes significantly to instilling values of tolerance, anti-radicalism, and respect for differences through three main strategies: integrating multicultural values into the curriculum, developing dialogical and inclusive learning methods, and strengthening the role of Islamic boarding schools and educational institutions as centers of religious moderation. The concept of wasathiyyah (middle path) is the philosophical foundation for the implementation of religious moderation in various educational institutions. The main challenges faced include uneven understanding among educators, limited teacher competence, cultural resistance, and a lack of systemic support. This study recommends strengthening the capacity of educators through continuous training, developing a more inclusive and contextual curriculum, and synergistic collaboration between the government, educational institutions, and the community to ensure that the values of religious moderation are continuously internalized in the life of Indonesia’s multicultural society.